Islamophobia in Malaysia: A Keyword-Based Analysis from Muslim Perspectives - Rafizah Daud; Nurlida Basir; Nurzi Juana Mohd Zaizi; Roslizawati Mohd Ramly; Melinda Melinda; Meor Mohd Shahrulnizam Meor Sepli (Asian Scholars Network, 2026)
Tier 3